2011
DOI: 10.1074/jbc.m111.233601
|View full text |Cite
|
Sign up to set email alerts
|

BabA-mediated Adherence Is a Potentiator of the Helicobacter pylori Type IV Secretion System Activity

Abstract: Chronic infection of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
136
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(142 citation statements)
references
References 50 publications
3
136
0
3
Order By: Relevance
“…Some studies suggest that patients infected with H. pylori strains expressing BabA are more likely to develop peptic ulcer disease or gastric cancer (14,15), particularly if the cagPAI is also present. These epidemiological observations have been supported by in vitro and in vivo mechanistic studies demonstrating that BabA-mediated attachment can potentiate CagA translocation by the T4SS (16) and promote autoantibody-mediated gastritis, parietal cell loss, and mucosa-associated lymphoid tissue in Leb transgenic mice (17).…”
mentioning
confidence: 54%
“…Some studies suggest that patients infected with H. pylori strains expressing BabA are more likely to develop peptic ulcer disease or gastric cancer (14,15), particularly if the cagPAI is also present. These epidemiological observations have been supported by in vitro and in vivo mechanistic studies demonstrating that BabA-mediated attachment can potentiate CagA translocation by the T4SS (16) and promote autoantibody-mediated gastritis, parietal cell loss, and mucosa-associated lymphoid tissue in Leb transgenic mice (17).…”
mentioning
confidence: 54%
“…It has been speculated for B. henselae that BadA and the VirB/D4 T4SS might interact synergistically in a way that BadA would mediate initial attachment to target cells, facilitate effector secretion, and manipulate cellular functions together with the Beps (322). The concept of such a relationship between an adhesin and a T4SS is reminiscent of the case for Helicobacter pylori, where host cell binding via the BabA protein was shown to amplify phenotypes associated with effector secretion (199). Although one could imagine that the enormous size and the dense surface layer of BadA may interfere with Bartonella effector secretion, the T-pilus of the planttargeting A. tumefaciens VirB/D4 T4SS is known to range from 1.4 m length on average up to even 4.5 m and would hence be much longer than BadA (8).…”
Section: The Primary Nichementioning
confidence: 96%
“…The binding between babA and Le b antigen is important not only for H. pylori to adhere to the stomach surface but also to anchor the bacterial secretion system (T4SS) to the host cell surface so that bacterial factors, including the CagA protein, can be effectively injected into the host cell cytosol. This interaction plays an important role in potentiating T4SS-mediated secretion, resulting in inflammation and IM [47,51], although we cannot address how specifically blood group type A affects H. pylori attachment to gastric epithelial cells. Animal experiments revealed that babA could stimulate the inflammatory cells to release more IL-8, CCL5 pro-inflammatory cytokines, and precancer-related factors (CDX2 and MUC2) [51].…”
Section: Resultsmentioning
confidence: 99%
“…This interaction plays an important role in potentiating T4SS-mediated secretion, resulting in inflammation and IM [47,51], although we cannot address how specifically blood group type A affects H. pylori attachment to gastric epithelial cells. Animal experiments revealed that babA could stimulate the inflammatory cells to release more IL-8, CCL5 pro-inflammatory cytokines, and precancer-related factors (CDX2 and MUC2) [51]. Since inflammatory response to H. pylori infection plays an important role in cellular proliferation and gastric mucosal damage, the upregulation of pro-inflammatory cytokines in people with chronic gastritis may be an important clinical implication in gastric carcinogenesis.…”
Section: Resultsmentioning
confidence: 99%